Peran Media Pembelajaran Matematika untuk Meningkatkan Motivasi Belajar Siswa - Ningsih, Putri; Susanti, Ely; Setiawati, Reni; Audrilia, Riski (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this research is to investigate how first-year class D students can be more motivated to learn by combining traditional classroom methods with modern technological devices. The research comprises four phases: design, implementation, observation, and assessment, making it an example of classroom action research. Eighteen male students and fifteen female students from the first year class D of State Elementary School 130 in Palembang participated in the study. Observation and interviews were utilized as tools. Descriptive qualitative analysis was conducted on all data. In cycle I, it was found that 60% of students had a desire to learn. Students' enthusiasm for learning increased to 96% in cycle II when they paid attention, completed tasks, and made connections with the teacher's content. Furthermore, we had traditional and digital resources to support this, including addition games 1-20, dice, and instructional films. The findings of cycle II indicate that the combination of traditional and technological media significantly enhances students' motivation to learn. Keywords: Professional Competence, Teacher